1991
DOI: 10.1111/j.1469-8137.1991.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a vesicular–arbuscular mycorrhizal fungus and rhizosphere micro‐organisms on manganese reduction in the rhizosphere and manganese concentrations in maize (Zea mays L.)

Abstract: SUMMARYMaize {Zea mays L. cv. Tau) plants were grown in a calcareous soil for six weeks in pots having separate compartments for growth of roots and vesicular-arbuscular (VA) mycorrhizal fungal hyphae. Soil was sterilized and either left non-inoculated (sterile treatment), or was inoculated with rhizosphere micro-organisms only (MO -VA) or with rhizosphere micro-organisms together with a VA mycorrhizal fungus [Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe (MO-I-VA)]. Concentrations of Mn in roots and shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
14

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(83 citation statements)
references
References 34 publications
3
64
0
14
Order By: Relevance
“…Different authors [2,20] have demonstrated a lower Mn uptake in plants mycorrhizal with arbuscular fungi compared with non-mycorrhizal ones. The availability of Mn for the plants is dependent on oxidation/reduction processes often driven by soil microorganisms capable to reduce Mn [22].…”
Section: Diameter (Mm)mentioning
confidence: 99%
“…Different authors [2,20] have demonstrated a lower Mn uptake in plants mycorrhizal with arbuscular fungi compared with non-mycorrhizal ones. The availability of Mn for the plants is dependent on oxidation/reduction processes often driven by soil microorganisms capable to reduce Mn [22].…”
Section: Diameter (Mm)mentioning
confidence: 99%
“…It has been speculated that high carbon demand of the fungus decreases root exudation, thus reducing substrate availahility for micro-organisms in the rhizosphere (Dixon et al, 1989;Pauhtz & Linderman, 1989). It has also been suggested that mycorrhizal infection could alter the composition of the root exudates (Kothari et al, 1991;Waschkies et al, 1994). However, it cannot be ruled out that the observed effect of mycorrhizal infection on the population density and physiological status of P. fluorescens 2-79RL was only indirect by favouring certain bacterial groups that are antagonistic to P. fluorescens 2-79RL.…”
Section: Discussionmentioning
confidence: 99%
“…tritium incorporation (Chnstenseii & Jakobseii, In most instances, arbuscular mycorrhizal (AM) 1993), and might influence the species composition infection increases the total number of aerobic of the soil microbial community by stimulating some bacteria m the rhizosphere (Bagyaraj & Menge, groups and decreasing others (Ames et al. 1984;1978;Mever & Linderman, 1986;Krishnaraj & Secilia & Bagyaraj,, 1987;Kothari et al, 1991;Sreenivasa' 1992;Posta, Marschner & Romheld, Christensen & Jakobsen, 1993;Posta et al, 1994). 1994), although no effect (Kothari, Marschner & 1986; Paulitz & Linderman, 1989;Klyuchnikov & Kozhevm, 1990 ;Posta et al, 1994;Waschkies et al, 1994).…”
mentioning
confidence: 99%
“…A atenuação da toxidez de Mn pode se dar tanto por efeitos indiretos da micorrização, como pela alteração da composição da comunidade microbiana da micorrizosfera (Kothari et al, 1991), ou, ainda, pelo aumento da absorção de P, principalmente em solos com alta capacidade de fixação de fosfatos (Li et al, 1991). Para limitar as interferências de outros microrganismos do solo e da fixação de P, este trabalho foi realizado em substrato arenoso autoclavado.…”
Section: Methodsunclassified